Electroconvulsive Therapy in Italy: Will Public Controversies Ever Stop?. Issue 3 (September 2016) - Buccelli, Claudio; Di Lorenzo, Pierpaolo; Paternoster, Mariano; D'Urso, Giordano; Graziano, Vincenzo; Niola, Massimo
Abstract : Background: The use of electroconvulsive therapy (ECT) is still very limited in Italy for ideological rather than scientific reasons. Objectives: To describe the public controversies surrounding ECT in Italy and to propose a plan of action to resolve the dispute. Methods: We describe the historical background and the current public controversies about ECT by reviewing the official documents issued by the entities involved in the debate and by reporting our personal experiences of ECT practice. Results: According to the highest legal and health authorities, there are no ethical reasons for doubting the licit nature of ECT. However, because of politically and ideologically based conflicts, public ECT centers are still lacking. The situation could further deteriorate because local initiatives are endeavoring to criminalize and ban the treatment. Conclusions: The enactment of specific regulations and guidelines concerning the use of ECT by the Italian government is highly warranted to increase the availability of the treatment. Education and information campaigns must strive to increase the knowledge of health professionals and the lay public regarding the safe and beneficial use of ECT. Abstract : Supplemental digital content is available in the text.